THU0578 Promoting Musculoskeletal Health in the Workplace – The Training Needs of Line Managers. (9th June 2015) - Erwin, J.; Howarth, J.A.; Edwards, K.J.; Woolf, A.D.
Abstract : Background: Musculoskeletal conditions (MSC) are a leading cause of absenteeism and presenteeism in the workplace. MSC account for 41% of all work-related illnesses in the UK. With an ageing population, increased retirement age and societal lifestyle changes, musculoskeletal (MSK) health in the workplace will play a major role in the extension of working lives. Objectives: To better understand the role of managers in promoting good MSK health in the workplace. Methods: 12 focus groups with a total of 78 participants were held with employees, employers and occupational health (OH) professionals from 4 large organisations in the health, local government, finance and food production sectors. Focus group transcripts were analysed using Thematic Analysis. Results: Barriers and facilitators to maintaining MSK health in the workplace which were cited by all participants included a lack of manager and employee awareness of the support and preventative measures for MSC available in the workplace and the lack of a holistic approach to MSK health problems. It was felt that existing health promotion activities in the work place did not explicitly address MSK health and that it needs to be prioritised and led by top levels of management to become embedded in the work culture. It was suggested that employees should be empowered to take responsibility for their own MSK health. Employees highlighted issues around the role of workplace culture, work practices and the availability of suitable equipment in maintaining MSK health. The pressure to achieve work targets and job insecurity were important barriers to taking actions to maintain MSK health. Being able to express concerns to managers and levels of empathy were perceived as important facilitators for MSK health. Managers saw MSK health as an important part of their role however, the emphasis was on health and safety regulatory aspects. Managers referred to OH but were sometimes uncertain on how to act on their advice. Managers recognised the need to be aware of the impact of work and workplace design on employee MSK health and to encourage good practice but perceived there to be a lack of time and budget to address these aspects. Managers and OH professionals suggested areas of training for line-managers including: basic information on anatomy; the impact of work on MSK health including workplace design, practices and employee activity; the impact of MSC on absenteeism and presenteeism; available support, understanding the role of OH and appropriate referral pathways; ability to do simple risk assessments; how to challenge detrimental work practices. Conclusions: The role of managers in promoting and maintaining MSK health in the workplace is an under-researched area. This qualitative study suggests a willingness of organisations and management to engage in this area. It also suggests that with improved training, managers could play a key role in the prevention of MSC and the promotion and maintenance of MSK health in the workplace. This study will be used to inform the development of: a model MSK Health Management Policy that can be adopted by organisations to provide a formal structure for the prevention and management of MSK problems; an assessment tool to enable organisations to understand the impact of activities and policy on employee MSK health; a training programme in MSK health for middle managers to prevent, and manage MSC in the workplace. Disclosure of Interest: None declared